UAV-Assisted Multispectral Dataset (60_metres) (Andhra Pradesh) - Saneev Das (20181741) (2025)
The multispectral payload used in this study was Micasense RedEdge-MX which comprises the blue, green, red, redEdge, and near-infrared bands. The UAV used to mount the multispectral camera was SNAP-M manufactured by CDSPACE. The DLS-2 module integrated with GPS, served as an essential attachment for the multispectral camera providing underlying light information. The quadcopter UAV used in this study had a payload capacity of up to 600 grams. The software integration with the multispectral camera was performed prior to the flight planning to ensure seamless operation. The study area was downsampled from the Andhra Pradesh province of Anantapur district and further to a cropland belonging to Puttaparthi region.